Adding Value to Customer Relationships through Corporate Blogs - Ahuja, Vandana (Indian Journal of Marketing, 2008)
As Consumer Generated Media (CGM) through blogs, wikis and online communities and forums becomes a force to be reckoned with, organizations understand the need to engage into meaningful interactions with their consumers. Consumer Generated Media has changed company relationships with their consumers from a unidirectional "attract customer" strategy to a culture of participation and co-creation. As consumer voices start echoing, organizations have woken up to the need to establish a meaningful interaction with their customers. As customer value addition moves into a new arena, Corporate Blogging is emerging as a new tool to evoke value perception in the mind of a customer. This paper aims to understand the concept of Corporate Blogging and its attempt to cater to the goals of Customer Relationship Management (CRM).